Ti6Al4V Titanium Alloy End Milling with Minimum Quantity of Fluid Technique Use - Garcia, U.; Ribeiro, M. V. [UNESP] (Taylor & Francis, 2016)
To reduce the use of cutting fluids in machining operations is a goal that has been searched in the industry due to environmental and human health problems that the cutting fluids cause. However, cutting fluids still promote the longer life of the cutting tool for many machining operations. This is the case of Ti6Al4V titanium milling operation using coated cemented carbide inserts. Therefore, the aim of this work is to study the feasible cutting conditions for use of minimal quantity of fluid (MQF) technique, i.e., conditions that make the tool life in MQF technique closer or higher than those obtained with the cutting without lubrication/cooling and cutting fluid jet without giving up productivity and the average roughness of the parts in the process. To achieve these objectives, several trials at Ti6Al4V end milling were performed by varying the cutting speed and feed rate with MQF application technique using vegetable cutting fluid compared with no lubrication/cooling and cutting with jet fluid to 8% aqueous emulsion. The main conclusion from this study was that the application of the MQF technique in Ti6Al4V end milling process increases the tool life and productivity and reduces the average surface roughness, while maintaining the same cutting conditions originally proposed in machining. Finally, microstructural analysis by scanning electron microscope (SEM) and energy dispersive spectrometry (EDS) was performed from cutting tools, and the main wear mechanisms when varying the lubrication/cooling systems employed were observed.
Keywords: Minimum quantity of fluid to the Ti6Al4V titanium; MQF technique; Optimization of cutting conditions; Ti6Al4V titanium milling